The impact of project team characteristics and client collaboration on project agility and project success: An empirical study. Issue 5 (October 2022) - Radhakrishnan, Abirami; Zaveri, Jigish; David, Dessa; Davis, John Stephen
Abstract: Although many companies pursue agile projects, extant literature reveals a lack of research on project agility determinants. This study examines the project team characteristics' impact on project agility and success using cross-sectional survey data from 292 agile projects. Using agile principles and complex adaptive systems theory, we find that project team autonomy, team diversity, and client collaboration have significant positive relationships with project agility. Project agility, in turn, has a significant positive relationship to project success. We measure project success by on-time completion, on-budget completion, specifications' attainment, and success rating by the project sponsor, client, and project team members. We find that project team members' adaptive performance partially mediates the relationship between project agility and success. These results guide agile project managers while facilitating team members to independently schedule their work, determine effective work methods, and develop innovative solutions. Moreover, they help agile managers recruit team members with relevant, diverse skill sets, domain knowledge, and expertise. Agile project managers must emphasize client collaboration in requirements gathering, designing, testing, and project reviews.